1999
DOI: 10.1530/eje.0.1410506
|View full text |Cite
|
Sign up to set email alerts
|

Fas and Fas ligand gene expression in autoimmune thyroiditis in BB/W rats

Abstract: Objective: Apoptosis via the Fas pathway is a potential mechanism for thyroid tissue destruction leading to clinical hypothyroidism in Hashimoto's thyroiditis (HT). Recent studies reported contradictory results regarding the regulation of Fas/Fas ligand (FasL) expression by cytokines in vitro. We therefore determined the Fas and FasL gene expression in the BioBreeding/Worcester (BB/W) rat thyroiditis model, which can be regarded as a model for HT. Methods: In order to obtain BB/W rats with spontaneous, iodine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Accordingly, the iodine-induced elevated expression of this apoptosis-related gene could play an important role also in the model of experimental thyroiditis in NOD mice. Our results agree with those of Bluher et al (22), who described high expression of Fas-L in BB/W rats after iodide administration. However, these authors have also detected an increase in Fas expression in comparison with control animals.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Accordingly, the iodine-induced elevated expression of this apoptosis-related gene could play an important role also in the model of experimental thyroiditis in NOD mice. Our results agree with those of Bluher et al (22), who described high expression of Fas-L in BB/W rats after iodide administration. However, these authors have also detected an increase in Fas expression in comparison with control animals.…”
Section: Discussionsupporting
confidence: 94%
“…The mechanisms involved have been related to direct toxicity as a consequence of high peroxide levels due to the strong expression of thyroid peroxidase in goiter-inducing conditions (7,21). Recently, many authors have related iodine to the development of apoptosis in humans (10,11) or in experimental models (22).…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of activated scavenger macrophages into the thyroid follicles, thus destroying the thyroid cells, is compatible with T H1 -mediated mechanisms [59]. Fas and Fas ligand (FasL) expression was higher in rats with lympholytic thyroiditis indicating a role of these apoptotic molecules in thyrocyte death [60]. …”
Section: Introductionmentioning
confidence: 99%
“…Production of interleukin 1β during thyroid inflammation induced upregulation of Fas expression and apoptosis in thyrocytes 20. In in vivo studies of BioBreeding/Worcester rats, Fas and FasL gene expression significantly increased in lymphocytic thyroiditis 21. Further animal studies showed that administration of plasmid DNA coding for FasL in thyroid follicular cells inhibited development of lymphocytic infiltration of the thyroid and induced the death of infiltrating T cells 22.…”
Section: Apoptosis and Autoimmune Thyroid Disordersmentioning
confidence: 99%